The role of sand lances ( Ammodytes sp.) in the Northwest Atlantic Ecosystem: A synthesis of current knowledge with implications for conservation and management - Michelle D. Staudinger; Holly Goyert; Justin J. Suca; Kaycee Coleman; Linda Welch; Joel K. Llopiz; David Wiley; Irit Altman; Andew Applegate; Peter Auster; Hannes Baumann; Julia Beaty; et al. (Fish and Fisheries, 2020)
The American sand lance ( Ammodytes americanus , Ammodytidae) and the Northern sand lance ( A. dubius , Ammodytidae) are small forage fishes that play an important functional role in the Northwest Atlantic Ocean (NWA). The NWA is a highly dynamic ecosystem currently facing increased risks from climate change, fishing and energy development. We need a better understanding of the biology, population dynamics and ecosystem role of Ammodytes to inform relevant management, climate adaptation and conservation efforts. To meet this need, we synthesized available data on the (a) life history, behaviour and distribution; (b) trophic ecology; (c) threats and vulnerabilities; and (d) ecosystem services role of Ammodytes in the NWA. Overall, 72 regional predators including 45 species of fishes, two squids, 16 seabirds and nine marine mammals were found to consume Ammodytes . Priority research needs identified during this effort include basic information on the patterns and drivers in abundance and distribution of Ammodytes , improved assessments of reproductive biology schedules and investigations of regional sensitivity and resilience to climate change, fishing and habitat disturbance. Food web studies are also needed to evaluate trophic linkages and to assess the consequences of inconsistent zooplankton prey and predator fields on energy flow within the NWA ecosystem. Synthesis results represent the first comprehensive assessment of Ammodytes in the NWA and are intended to inform new research and support regional ecosystem‐based management approaches.